(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study was performed to investigate the dual mediating effects of growth mindset and impulsiveness between smartphone addiction and depression of workers. Method/Statistical Analysis: The major subjects of this study were 286 employees of 20 work-places in Seoul, Daejeon, Chungnam province, and Chungbuk areas. The collected data were analyzed using t-test, ANOVA, correlation analysis, dual mediation effect analysis by SPSS PC+ Win. 25 and SPSS PROCESS macro 3.4. Findings: First, there was no significant difference in depression according to the general characteristics of the subjects. Second, the growth mindset had a negative correlation with impulsiveness and depression. And Impulsiveness had a positive correlation with depression. Third, mediating effect analysis revealed that there was a dual mediation effect of growth mindset and impulsiveness between smartphone addiction and depression of workers. Improvements/Applications: Based on these findings, growth mindset is expected to act as a major defensive factor. And, we discussed ways to reduce depression caused by smartphone addiction